PENGARUH SUPERVISI AKADEMIK, MOTIVASI KEPALA SEKOLAH DAN LINGKUNGAN KERJA TERHADAP PENINGKATAN KINERJA GURU DI SMA YADIKA 8 JATIMULYA BEKASI - Elsye; Darlius (Jurnal Satya Mandiri Manajemen dan Bisnis, 2016)
This study aims to describe and analyze the influence of the academic supervision, motivation of principal, and the work environment to the improvement of teacher performance and de termine which variables are most strongly affect the performance of teachers. The study population was 60 high school teachers Yadika 8 Jatimulya and the entire population of the research sampled . Samples were taken with the Proportional techniques clust errandom sampling. Techniques of data collection using questionnaire instruments. Validity of the items tested by product moment correlation person, while the coefficient of reliability was tested with Cronbach alpha formula. Strong relationship occurs between the academic supervision, motivation of principal and the work environment with teacher performance improvement. Variable the motivation of principal has more influence on the improvement teacher performance than academic supervision and the work environment. Furthermore, there is simultaneously a significant positive effect of joint between the academic supervision, motivation of principal and the work environment to the improvement teacher performance. A partial significant positive effect on improving performance of academic supervision, motivation of principal and the work environment to the improvement of teacher performance.